EFEKTIVITAS MANAJEMEN RISIKO DALAM PEMBIAYAAN MUDHARABAH DAN MUSYARAKAH - Lia Wardati; Muhammad Ismail; Nazwa Hasanatul Hikmah; Muhammad Aldi Akbar; Erwan Setyanoor (Ahsan: Jurnal Ilmiah Keislaman dan Kemasyarakatan, 2025)
The Islamic economy, based on the principles of justice, equality, and the prohibition of usury, offers alternative financing through profit-sharing contracts, particularly mudharabah and musyarakah. These contracts are key instruments in Islamic banking; however, their implementation in Indonesia still faces challenges, including the dominance of non–profit-sharing products, financing risks, and regulatory limitations. This study aims to analyze the implementation of risk management in mudharabah and musyarakah financing. The research method employs a library research approach with qualitative descriptive analysis. Data were collected through documentation studies of primary and secondary literature, including books, journal articles, DSN-MUI fatwas, and relevant regulations. Data analysis was conducted using content analysis, which involved identifying themes, classifying information, and synthesizing findings. The results show that risk management in mudharabah and musyarakah includes the processes of risk identification, evaluation, and mitigation, tailored to the nature of each contract. Mitigation strategies include customer feasibility analysis, business monitoring, document verification, and limited use of collateral. Although these contracts have the potential to support inclusive economic development, their application still requires strengthening public knowledge, improving regulations, and implementing systematic risk management to optimize their benefits.